Validation of a Chinese Version of the Attitudes Toward Prisoners Scale. (November 2019) - Chui, Wing Hong; Cheng, Kevin Kwok-yin
Using a Hong Kong–sourced sample of participants, this study set out to validate the Chinese version of the Attitudes Toward Prisoners (ATP-C) Scale and evaluate its psychometric properties. To provide further evidence for the ATP-C Scale's validity, it was then administered to three groups varying in their volunteering experience in Hong Kong. Exploratory factor analysis revealed a four-factor structure that differs from the unidimensional model proposed by the scale developers. Cronbach's alpha values were satisfactory for all four subscales, and construct validity of the ATP-C Scale was also assessed with a second sample of participants. Implications for the assessment of attitudes toward prisoners away from a one-dimensional spectrum and further directions for cross-cultural studies on related topics are discussed.